2016
DOI: 10.1007/s00726-016-2367-0
|View full text |Cite
|
Sign up to set email alerts
|

C-type natriuretic peptide prevents kidney injury and attenuates oxidative and inflammatory responses in hemorrhagic shock

Abstract: Oxidative stress induced by hemorrhagic shock (HS) initiates a systemic inflammatory response, which leads to subsequent kidney injury. This study assessed the efficacy of c-type natriuretic peptide (CNP) in attenuating kidney injury in a rat model of hemorrhagic shock and resuscitation (HS/R). Sodium pentobarbital-anesthetized adult male Wistar rats underwent HS induced by the withdrawal of blood to a mean arterial pressure of 30-35 mmHg for 50 min. Then, the animals received CNP (25 μg/kg) or vehicle (saline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…CNP reduces the number of macrophages, neutrophils, and lymphocytes accumulating in the lungs of mice exposed to bleomycin in a model of pulmonary hypertension [115]. In a rat model of haemorrhagic shock, CNP reduces markers of oxidative stress and the expression of tumour necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β in the kidney, suggesting it may improve symptoms of acute renal injury associated with this condition [116]. Furthermore, studies performed using transgenic mice overexpressing CNP in endothelial cells suggest that CNP regulates inflammation associated with obesity.…”
Section: Cnp Inhibits Inflammation and Slows The Development Of Atmentioning
confidence: 99%
“…CNP reduces the number of macrophages, neutrophils, and lymphocytes accumulating in the lungs of mice exposed to bleomycin in a model of pulmonary hypertension [115]. In a rat model of haemorrhagic shock, CNP reduces markers of oxidative stress and the expression of tumour necrosis factor (TNF)-α, interleukin (IL)-6, and IL-1β in the kidney, suggesting it may improve symptoms of acute renal injury associated with this condition [116]. Furthermore, studies performed using transgenic mice overexpressing CNP in endothelial cells suggest that CNP regulates inflammation associated with obesity.…”
Section: Cnp Inhibits Inflammation and Slows The Development Of Atmentioning
confidence: 99%
“…It was established that intravenous administration of CNP (25 mg/kg) to rats with hemorrhagic shock prevents an increase in TNF-a, IL-1b and IL-6 content in the kidney. 130 Investigators found that CNP reduces secretion of MCP-1 and plasminogen activator inhibitor-1 (PAI-1) by cardiac fibroblasts. 131 They suggest that a decrease in MCP-1 and PAI-1 secretion is involved in the antifibrotic effect of the peptide.…”
Section: Anti-inflammatory Effect Of Natriuretic Peptidesmentioning
confidence: 99%
“…CNP infusion to this model lowered the myeloperoxidase activity and decreased the expression of TNF-α, IL-6, and IL-1β in the kidneys. CNP treatment suppressed oxidative stress, ameliorated the inflammatory response, and caused acute kidney injury [92]. Investigators suggested that they demonstrated CNP infusion's inhibitory effect on the generation of reactive oxygen species (ROS) and pro-inflammatory cytokines after hemorrhagic shock induction and subsequently suppressed the activation, recruitment, and adherence of neutrophils in the kidney.…”
Section: Cnp During Inflammatory Disease Activitymentioning
confidence: 99%